Antigenotoxic potential of rutin and quercetin in Swiss mice exposed to gamma radiation - Shrikant L Patil; Nageshwar B Rao; HM Somashekarappa; KP Rajashekhar (Biomedical Journal, 2014)
Background: Ionizing radiation induces a variety of genetic damages through the formation free radicals such as reactive oxygen species (ROS). Appropriate antioxidant intervention may inhibit or reduce free radical toxicity and thus offer protection against radiation. Rutin (RUT) and quercetin (QRT) are flavonoids known to be potent dietary antioxidants. Methods: The present study tested the antigenotoxic effect of RUT and QRT in vivo against radiation- induced chromosomal damage. Swiss albino mice were administered orally with RUT and QRT (10 and 20 mg/kg b.wt.) once daily for five consecutive days. One hour after the last administration of RUT and QRT on the fifth day, the animals were whole body exposed to 3 Gy gamma radiation. The anti-genotoxic potential was assessed in terms of chromosomal aberrations, micronucleus test, and alkaline comet assay. Results: Significant decline in dicentric formation was observed in RUT and QRT treated group. Further, the antigenotoxic potential of RUT and QRT caused a significant (p < 0.001) reduction in micronucleated polychromatic, normochromatic erythrocytes; increased PCE/NCE ratio was observed in the RUT and QRT treated group. Administration of RUT and QRT before irradiation resulted in a significant (p < 0.01) decrease in the DNA damage at the post-irradiation time when compared with irradiation alone group. Conclusions: Present findings demonstrate the potential of RUT and QRT in mitigating radiation-induced mortality and cytogenetic damage, which may be attributed to scavenging of radiation-induced free radicals.